Enhancement of enzymatic properties of T1 lipase by saturation mutagenesis at glutamine 114 - Ab. Wahab, Roswanira (2012)
Rational design of the recombinant T1 lipase gene by saturation mutagenesis on the oxyanion Gln114 was successfully carried out to afford a library of twenty lipase variants. The objective of the study was to investigate the impact of a single point saturation mutagenesis at the oxyanion Gln114 on the enzymatic behavior and enantioselectivity of T1 lipase. Furthermore, the effect of such mutation in the active site of T1 lipase has never been studied. The selection of the mutation site was based on the close proximity of Gln114 residue to the catalytic machinery and is intimately involved in the substrate-enzyme interaction. It was hypothesized that the mutation could invoke substantial changes in the catalytic efficiency and enantioselectivity of T1 lipase. Computational assessment using YASARA, FoldX and Voronoia 1.0, found significant variations in potential energy, total cavity and protein compactness. It was anticipated that Q114L and Q114M are more stable than T1 lipase. Profiling of the seven enzyme behaviors found Q114L to show a 10oC increase in optimum temperature as comparedto 70oC in T1 lipase. Amino acids of small side-chains, polar, acidic and basic,generally, caused reduction in the optimum temperatures. A downward shift in pH optimum from pH 9 to pH 8 was observed when non-polar and basic amino acids were replaced into Gln114. pH optimum of lipases were unchanged upon substitution with polar amino acids. Specificities towards hydrolysis of natural oils were also very different from one lipase to another, with an overall reduction in lipase activity. Various chemical reagents affected the lipase variants, namely, organic solvents, surfactants, metal ions and inhibitors/chelating agents. Lipases substituted with nonpolaramino acids exhibited higher frequency of improved enzyme properties. Their non-polar nature that does not interact strongly with charged molecules in the active site could be the contributing factor. Less enzyme deactivation was observed in hydrophobic solvents as compared to hydrophilic ones. This is due to the nature of hydrophilic solvents that tend to partition preferentially into the cytoplasmic membrane, while hydrophobic solvents tend to partition away. The enzymes showed preference towards surfactant Span 20, KI and SC, as well as catalysis activation by Sr(II). Substitution of Leu and Met into Gln114 resulted in variants Q114L and Q114M that showed the most number of cumulative enhancements and were more competent than T1 lipase. In the esterification of menthol with butyric anhydride, T1 lipase afforded a higher yield of 99.3% menthyl butyrate as compared to 75.1% in Q114L. The former gave optimum conditions at 60oC, 2.53 mg enzyme, molar ratio of butyric anhydride:menthol at 1:1 to 1.5:1 and incubated for 13 h and 15 min, while the latter were at 67.5oC, 3 mg enzyme, substrate molar ratio at 3.5:1 and incubated for 13 h and 21 min. The higher yield could be attributed to the hydrophilic nature of the substrates that could interact better with the hydrophilic Gln114 in T1 lipase. Also, the higher temperature in Q114L-catalyzed reactions could have increased evaporation of menthol, hence, lowering its concentration in the reaction. In the enantioselectivity study for the enzymatic resolution of racemic ibuprofen using oleyl alcohol, variants Q114L and Q114M were selected for this purpose. Mutation at oxyanion Gln114 had changed enantioselectivity, whereby Q114M was the most enantioselective followed by T1 lipase and Q114L. Hence, it can be concluded that saturation mutagenesis of oxyanion Gln114 had significantly changed the enzymatic behavior and enantioselectivity of T1 lipase. The observed cumulative improvement in lipase properties mostly came from substitutions with mainly medium-sized non-polar hydrophobic amino acids. The most catalytically competent variants were found to be Q114L and Q114M, respectively. On the other hand, substitution with hydrophilic, basic, acidic and bulky side-chain amino acids affected T1 lipase negatively. Hence, it is recommended that future mutational studies to avoid using these amino acids as it would only lead to inferior enzyme qualities.